Comparison of effects of unfractionated heparin and low molecular weight heparin on skin wound healing of rats - Durmaz,Can Engin (2012)
PURPOSE: To compare the effects of unfractionated heparin (UH) and a low molecular weight heparin (LMWH) on skin wound healing of rats. METHODS: Forty eight male Sprague-Dawley rats underwent 8mm full thickness dorsal skin wounds and were randomly assigned to three equal groups. In experimental group A, heparin sodium was injected at a concentration of 1000U/kg. In experimental group B, enoxaparin was injected at a concentration of 1mg/kg. Physiologic saline (0.5ml) was administered to the control group. Injections were made subcutaneously, once daily, for seven days. At 7th and 10th days tissue samples were taken from all rats. Histologic examination of these tissues was made under light microscope and scored. RESULTS: Histological examination showed a significant difference between the 7th and 10th day groups in wound healing. It was observed that wound healing of LMWH injected group is better. This difference is statistically significant at 10th day. CONCLUSIONS: Daily administration of single doses of unfractionated heparin and a low molecular weight heparin improves wound healing positively. Low molecular weight heparin induces wound healing more than unfractionated heparin.